PERAN ORANG TUA DALAM MENDORONG MOTIVASI BELAJAR SISWA DI SMP PLUS SUNAN KALIJOGO TULANG BAWANG - Sintya Eka Wahyuni; Ahmad Fauzan; Fisman Bedi (STKIP Subang, 2023)
This study aims to determine the role of parents in encouraging children's learning motivation at SMP Plus Sunan Kalijogo Tulang Bawang. The research method used is descriptive research method with a qualitative approach. Data collection techniques and instruments are interviews, observation and documentation. Research results that there are five roles of parents in motivating student learning, namely providing encouragement, giving awards or prizes, creating a conducive or comfortable environment, providing support so as not to give up easily, introducing new things that trigger student curiosity. And the obstacles experienced by parents in carrying out their role to motivate student learning are limited space so that parents cannot provide a special study room for students and the economic limitations of each parent so that parents are not optimal in carrying out their role as a motivator.